KEBAHASAAN SINEMATIK BERNUANSA PLURALITAS DALAM IKLAN BNI TAPLUS ANAK - Rustono Farady Marta; Patricia Robin (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2019)
Early education introduces children to how to manage money, especially since growing up to become a person who values money more. Related to this, PT. Bank Negara Indonesia, Tbk (BNI) released the BNI Taplus Anak program for children aged 0 to 17 years. To proclaim the service, advertisements were made that were very close to the reality of the lives of parents and children. This advertisement tells a group of bands with the name